Of teamwork, faith, and trust in West Sumatra - Colfer, C.J.P. (Wadsworth Publishing Company, 2000)
This chapter describes Colfer’s experience doing fieldwork in the village of Pulai, in West Sumatra. She describes the early stages of her research when the community approached her with great suspicion, fearing that she was there to proselytize the Christian religion. She documents her persistent and initially unsuccessful efforts to gain the people’s trust, culminating when she found herself confronted with a woman apparently dying in childbirth. Her ready offer of transportation and funding marked the end of the community’s suspicion, and the beginning of a satisfying and enjoyable research experience.